APPLICATION OF BAMBOO PILES IN ATHLETIC TRACK CONSTRUCTION - Reynold Andika Pratama; Ervina Yuliyanti; Savira Septiarini; Gita Puspa Artiani (International Journal Multidisciplinary Science, 2025)
This study explores the application of bamboo piles as a sustainable ground improvement technique in the construction of an athletic track at the Malabar National Athletic Training Center in Pangalengan, West Java. Utilizing a qualitative case study approach, the research documents the implementation methods, technical considerations, and performance outcomes of bamboo pile foundations in addressing geotechnical challenges posed by soft clay soils and high groundwater levels. The bamboo piles, made from Gigantochloa apus, were systematically prepared, treated with borax-boric acid for durability, and installed in a triangular grid pattern to enhance soil bearing capacity and minimize settlement. The integrated foundation system, combining bamboo piles with gravel layers, drainage systems, and a synthetic track surface, met the International Association of Athletics Federations (IAAF) performance criteria, achieving a bearing capacity improvement of 180-220% and maximum settlement of 12 mm. The approach offered significant economic benefits, with 35-45% cost reductions compared to conventional concrete piles, and environmental advantages, including a 60-70% lower carbon footprint. This research underscores the viability of bamboo piles as a cost-effective, environmentally friendly solution for specialized construction, bridging traditional knowledge with modern engineering practices. Recommendations for future applications include rigorous geotechnical investigations, quality control, and long-term performance monitoring to ensure reliability.